1965
DOI: 10.1055/s-0038-1656297
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Antithrombin Deficiency Causing Thrombophilia

Abstract: SummaryBlood coagulation systems were studied in members of a family with remarkably high incidence of thrombo - embolic diseases. Thrombotic episodes most often occurred as deep venous thrombosis in the legs, with the first attack at the age of 10-25 years.Pro coagulant factor activities were found within normal variation ranges.Plasma antithrombin III (progressive antithrombin) activity was abnormally low in members with history of thrombosis and in some of their children, with an average level of about 50 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
385
1
20

Year Published

1979
1979
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 810 publications
(410 citation statements)
references
References 26 publications
4
385
1
20
Order By: Relevance
“…3 This initial observation has since been confirmed by other groups from different parts of the world.4-6 The pattern of inheritance of Our understanding of the molecular basis of the inherited disorders of antithrombin has been greatly facilitated by the cloning and characterization of the antithrombin gene. 1O -12 It is now recognized that the antithrombin molecule has two important functional domains, namely a thrombin binding domain and a heparin binding domain."…”
Section: Prevalencementioning
confidence: 90%
See 1 more Smart Citation
“…3 This initial observation has since been confirmed by other groups from different parts of the world.4-6 The pattern of inheritance of Our understanding of the molecular basis of the inherited disorders of antithrombin has been greatly facilitated by the cloning and characterization of the antithrombin gene. 1O -12 It is now recognized that the antithrombin molecule has two important functional domains, namely a thrombin binding domain and a heparin binding domain."…”
Section: Prevalencementioning
confidence: 90%
“…The association between familial antithrombin deficiency and venous thromboembolism was first recognized in a Norwegian family by Egeberg in 1965. 3 This initial observation has since been confirmed by other groups from different parts of the world.4-6 The pattern of inheritance of Our understanding of the molecular basis of the inherited disorders of antithrombin has been greatly facilitated by the cloning and characterization of the antithrombin gene.…”
Section: Prevalencementioning
confidence: 99%
“…Similarly, when plasma kallikrein (final concentration, 32 ,ug/ml) was incubated with either a2PI (70,ug/ml), Clinh Previous studies from many laboratories have shown that the specificities of these inhibitors are broad and to some extent overlapping. For example, Clinh inhibits not only the action of CYbut also the actions of plasmin (26), plasma kallikrein (26), HFf (25), and act.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Clinh deficiency is associated with hereditary angioneurotic edema (30), a1-anti-trypsin deficiency with pulmonary emphysema and hepatic disease (31), and antithrombin III deficiency with thrombosis (32). Thus, the physiologic role of each inhibitor appears to be quite specific, whereas each inhibitor demonstrates a broad in vitro specificity.…”
Section: Methodsmentioning
confidence: 99%
“…1 The inhibitory effect of AT, due to the almost irreversible trapping of target proteases, is strongly enhanced by natural glycosaminoglycans such as heparin.…”
Section: Three Novel Mutations Of Antithrombin Inducing High-moleculamentioning
confidence: 99%